Participação do cidadão no processo administrativo: garantia fundamental do Estado Democrático de Direito - Oliveira, Ocimar Barros de (2011)
This dissertation addresses citizen participation in general administrative proceedings. It aims to analyze the subject under the law and doctrinal texts on administrative process, defining the current concepts of participation and citizenship, as well searching and comparing legal texts and doctrinal literature. During the study we sought answers to some questions such as: When and how citizens can intervene in the administrative process? Which are the participation and controlling instruments in administrative process that the citizen can make use of? Which dangers and limits of participation? We noted that citizen actually can and should participate actively in administrative decisions conducting, whether as a part, as an interested third or as part of organized social groups with power of representation. In the participation the citizen must also respect the limits imposed by legislation, both constitutional and infra.